Hybrid Internal Vth Cancellation Rectifiers for RF Energy Harvesting - Munir A. Al-Absi (IEEE Access, 2020)
This paper presents two Internal Threshold Voltage (IVC) cancellation schemes for rectifiers used in RF energy harvesting: N-stage IVC based rectifier and IVC based rectifier with Self Vth Cancellation (SVC). The presented rectifiers reduce the threshold voltage of the transistors and deliver a high-rectified output voltage at an input frequency of 402MHz. Tanner TSPICE simulation tool in 0.18μm TSMC CMOS technology is used to confirm the functionality of the proposed designs. Simulation results show that the proposed design is superior to the previously published works in reducing the MOSFET threshold voltage and delivering a rectified high output voltage at an input voltage of 200mV and frequency of 402 MHz.